PENGUATAN PENDIDIKAN KARAKTER PADA SISWA SEKOLAH DASAR MELALUI PEMANFAATAN LITERASI DIGITAL - Sherli Pentianasari; Fadhilah Dwi Amalia; Badruli Martati; Nisa’ Aqidatul Fithri (PGSD Universitas Muhammadiyah Cirebon, 2022)
ABSTRACT Strengthening character education needs to be instilled in students in the era of rapid technology that brings positive and negative influences. Where this development must also be balanced with the cultivation of character education from an early age to prevent students from the crisis of character values, among others, can be done through digital literacy. This study aims to determine the benefits of digital literacy in growing and strengthening the character education of elementary school students. The research method uses descriptive-qualitative method with a literature study approach, the data source is obtained from the results of the analysis and conclusions obtained from the journal. The results of the analysis of this study are in strengthening the character education of elementary school students in the 21st century, digital literacy plays an important role as a supporting media because students tend to be more interested in technology, the internet, social media, and others, and are supported by thematic learning taught in elementary schools. which includes the integration of character values ??in each lesson. The conclusion of this study is that the use of digital literacy is able to strengthen character values ??with balanced supervision from parents and teachers in its use. Keywords: digital literacy; thematic learning; character building ABSTRAK Penguatan pendidikan karakter perlu ditanamkan kepada siswa di era pesatnya teknologi yang membawa pengaruh positif dan negatif. Dimana perkembangannya ini juga harus diimbangi dengan penanaman pendidikan karakter sejak dini untuk menghindarkan siswa dari krisisnya nilai karakter, antara lain dapat dilakukan melalui literasi digital. Penelitian ini bertujuan untuk mengetahui manfaat literasi digital dalam menumbuhkan dan menguatkan pendidikan karakter siswa sekolah dasar. Metode penelitian yang digunakan adalah metode deskriptif-kualitatif dengan pendekatan studi pustaka, sumber data diperoleh dari hasil analisis dan simpulan yang diperoleh dari jurnal. Hasil analisis dari penelitian ini adalah dalam menguatkan pendidikan karakter siswa sekolah dasar di abad 21 literasi digital berperan penting sebagai media pendukung karena siswa cenderung lebih tertarik dengan teknologi, internet, media sosial, dan lainnya, serta di dukung dengan pembelajaran tematik yang diajarkan di sekolah dasar yang memuat integrasi nilai-nilai karakter di setiap pembelajarannya. Kesimpulan dari penelitian ini adalah pemanfaatan literasi digital mampu menguatkan nilai karakter siswa dengan diimbangi pengawasan dari orang tua dan guru dalam penggunaannya Kata Kunci: literasi digital; pembelajaran tematik; pendidikan karakter